PENGARUH UKURAN, PERTUMBUHAN DAN RISIKO PERUSAHAAN TERHADAP NILAI PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ 45 DI BURSA EFEK INDONESIA - Putri, Atika; Djazuli, Abid; Riyah, Choiriyah (Universitas Muhammadiyah Palembang, 2019)
This study aimed to determine the effect of companies’ size, growth and risk on the value of companies incorporated in the LQ 45 index on the Indonesia stock exchange. The type of research used in this study is associative. The population used in this study was 68 companies. Sample which was selected based on the Purposive Sampling method was 22 companies. The analytical tool used in this study was the classic assumption test, multiple linear regression analysis, and hypothesis testing using the F test (simultaneous) and the T test (partially) with a significant level of 5%. The results of this study indicated that there was an effect of companies’ size, growth, and risk together on the value of companies incorporated in the LQ 45 index on the Indonesian stock exchange. While partially, the size and risk variables had a negative and significant effect on the value of companies incorporated in the LQ 45 index on the Indonesia stock exchange. While growth had a negative and insignificant effect on the value of companies incorporated in the LQ 45 index on the Indonesian stock exchange.